The Application of Virtual Simulation Technology in Scaling and Root Planing Teaching - Shiwen Wu; Li Gao; Jiarun Fu; Chuanjiang Zhao; Panpan Wang (Elsevier, 2024)
ABSTRACT: Background: Virtual simulation (VS) technology has been widely utilised in various aspects of oral education. This study aimed to evaluate the impact of VS technology in a scaling and root planing (SRP) teaching programme and explore an effective teaching approach. Method: A total of 98 fourth-year undergraduates from Guanghua School of Stomatology at Sun Yat-sen University were enrolled in this study and randomly assigned to either the VS teaching group or the traditional teaching (TT) group. All participants received SRP training before undergoing an operational examination. Subsequently, questionnaires were administered to both students and teachers involved in the programme to assess the teaching effect and fidelity of the VS training system. Unpaired Student t test was used to analyse the final test scores and residual rates amongst students. Results: The overall residual rate of the calculus in the VS group was significantly lower than that in the TT group (48.81% ± 13.50% vs 56.89% ± 13.68%, P<.01). The difference was particularly notable in posterior teeth, proximal surfaces, and deep pockets. Additionally, the VS group students achieved higher final grades compared to the TT group (86.92 ± 6.10 vs 83.02 ± 6.05, P<0.01). In terms of teaching effectiveness assessment, the VS group students provided higher scores than the TT group, except in the areas of mastery of position, finger rests, and efficiency. Conclusions: The implementation of VS technology demonstrated improvements in students' performance in SRP teaching. Therefore, a novel integrated pedagogic approaches method that combines VS technology with traditional teaching approaches could be further explored in future training programmes.